Comparison of maternal and neonatal outcomes in twin pregnancies according to delivery types: vaginal delivery or Cesarean delivery? - Gökçe Turan; Berna Aslan Çetin; Ezgi Turgut; Zelal Aydın; Erhan Demirdağ; Tamella Taghiyeva (Perinatal Medicine Foundation, 2022)
Objective: Our aim was to compare the maternal and neonatal outcomes of twin pregnancies, which result in vaginal delivery (VD) and Cesarean section (CS), and the factors affecting the decision of CS. Methods: Twin pregnancies between 30 and 39 weeks who gave birth in a tertiary center were included in the present study. The demographic data and maternal and neonatal outcomes of the patient groups who gave birth <32 weeks, 32-37 weeks, and >37 weeks were recorded and compared according to the type of birth. Results: A total of 1209 patients were included in the study. The 1- and 5-minute Apgar scores of the 1st and 2nd fetuses in twin pregnancies <32 weeks of gestation were higher in the CS group at a statistically significant level (p=0.007, p=0.010, p=0.001, and p=0.003, respectively). The 1- and 5-minute Apgar scores of the 2nd fetuses of the pregnant women >37 weeks of age were higher in the VD group at a statistically significant level (p=0.039 and p=0.032, respectively). The newborn intensive care unit (NICU) admission rates of 1st fetus and 2nd fetus in the groups of <32 weeks, 32-37 weeks, and >37 weeks were higher in those born by CS at a statistically significant level when compared to those born by VD (1st fetus p<0.001, p<0.001, p=0.016, respectively; 2nd fetus p<0.001, p<0.001, p=0.012, respectively). Conclusion: It must be kept in mind that twin pregnancies have high risks. However, vaginal delivery can be considered as a safe and reasonable option in appropriately selected cases and in the presence of experienced obstetricians by being careful about maternal and neonatal complications which might occur.